The biology and treatment of Merkel cell carcinoma: current understanding and research priorities. Issue 12 (December 2018) - Harms, Paul; Harms, Kelly; Moore, Patrick; DeCaprio, James; Nghiem, Paul; Wong, Michael; Brownell, Isaac
Abstract Merkel cell carcinoma (MCC) is a rare and aggressive skin cancer associated with advanced age and immunosuppression. Over the past decade, an association has been discovered between MCC and either integration of the Merkel cell polyomavirus, which likely drives tumorigenesis, or somatic mutations owing to ultraviolet-induced DNA damage. Both virus-positive and virus-negative MCCs are immunogenic, and inhibition of the programmed cell death protein 1 (PD-1)–programmed cell death 1 ligand 1 (PD-L1) immune checkpoint has proved to be highly effective in treating patients with metastatic MCC; however, not all patients have a durable response to immunotherapy. Despite these rapid advances in the understanding and management of patients with MCC, many basic, translational and clinical research questions remain unanswered. In March 2018, an International Workshop on Merkel Cell Carcinoma Research was held at the US National Cancer Institute, at which academic, government and industry experts met to identify the highest-priority research questions. Here, we review the biology and treatment of MCC and report the consensus-based recommendations agreed upon during the workshop. Merkel cell carcinoma (MCC) is a rare and aggressive form of nonmelanoma skin cancer. The availability of immune checkpoint inhibition has improved the outcomes of a subset of patients with MCC, although many unmet needs continue to exist. In this Consensus Statement, the authors summarize developments in our understanding of MCC while also providing consensus recommendations for future research.